Ascese econômica: a constituição do estudante-empreendedor - Gilaverte, Ana Paula (2021)
This research analyzes the perspective of the production of subjectivity in the point of view of students regarding the self-constitution as an entrepreneurial student. This process, in the school environment, is established through the dissemination of discourses about entrepreneurship, autonomy and student protagonism. The proposed problem is how economic ascesis constitutes the entrepreneur student´s subjectivity of himself. It is a problem linked to the discourse of entrepreneurship that currently permeates the school context and the conceptions of entrepreneurial education targeting the constitution of the subjectivity of students as entrepreneurs of themselves. The issue is translated at public schools by the adoption of an entrepreneurial posture, which privileges the introduction of values based on autonomy, competent formation, self-regulation, development of social-emotional skills and individual co-responsibility, considered as pillars of the 21st century education. The proposed methodology is hermeneutical, based on the texts of Michel Foucault, aiming to observe the modalities in which students are enunciated as subjects of the entrepreneurial discourse in a subjective relationship of the self-constitution as an entrepreneur student. For the results, the discourses circulating in the school which make up the profile offered to the students are contextualized, so that they constitute themselves as an entrepreneurial subject according to the contemporary demands.